ASP.NET Core MVC 2.0 Cookbook - Polat, Engin; Polat, Engin; Belkheraz, Stephane (Packt Publishing, 2018)
Learn to implement ASP.NET Core features to build effective software that can be scaled and maintained easilyAbout This BookPractical solutions to recurring issues in the web development worldRecipes on the latest features of ASP.Net Core 2.0Coverage of Bootstrap, Angular, and JavaScript lets you supercharge your frontendWho This Book Is ForThis book is written for the ASP.NET developer who wants to deliver professional-standard software, quickly and efficiently. It's filled with hands-on recipes, practical advice, and guidance to help developers with every aspect of the ASP.NET development cycle. Whether you've just started out or are a seasoned pro, the Asp.Net Core 2.0 Cookbook is written for you.What You Will LearnBuild ASP.Net Core 2.0 applications using HTTP services with WebApiLearn to unit-test, load test, and perform test applications using client-side and server-side frameworksDebug, monitor and troubleshoot ASP.Net Core 2.0 applications using popular toolsReuse components with NuGet and create modular components with middlewareCreate applications using client-side technologies such as HTML5, JavaScript, jQuery, and AngularBuild responsive and dynamic UIs for your MVC apps using BootstrapLeverage tools like Karma, Jasmine, QUnit, xUnit, Selenium, Microsoft Fakes, and Visual Studio 2017 EnterpriseIn DetailThe ASP.NET Core 2.0 Framework has been designed to meet all the needs of today's web developers. It provides better control, support for test-driven development, and cleaner code. Moreover, it's lightweight and allows you to run apps on Windows, OSX and Linux, making it the most popular web framework with modern day developers.This book takes a unique approach to web development, using real-world examples to guide you through problems with ASP.NET Core 2.0 web applications. It covers Visual Studio 2017- and ASP.NET Core 2.0-specifc changes and provides general MVC development recipes. It explores setting up .NET Core, Visual Studio 2017, Node.js modules, and NuGet. Next, it shows you how to work with Inversion of Control data pattern and caching. We explore everyday ASP.NET Core MVC 2.0 patterns and go beyond it into troubleshooting. Finally, we lead you through migrating, hosting, and deploying your code.By the end of the book, you'll not only have explored every aspect of ASP.NET Core MVC 2.0, you'll also have a reference you can keep coming back to whenever you need to get the job done.Style and approachAsp.Net Core 2.0 has been redesigned to meet the needs of today's web developers. Open-source, cross-platform, and fully integrated with the most powerful front-end frameworks, it still has all the benefits of ease and speed of development that have made it one of the most popular web frameworks in production today. Asp.Net Core 2.0 Development Cookbook takes a unique approach to web development. Based around the tasks that you will be using every day when making websites, it will guide you through all the common problems you'll face when developing web applications.